Faktor yang memengaruhi Perilaku Masyarakat Pencegahan Penyakit ISPA di Puskesmas Madat Kabupaten Aceh Timur - Faisal Faisal; Nuraini Nuraini; Anto Anto (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2021)
Acute Respiratory Infections (ARI) is one of the most infectious diseases and causes of death in children in developing countries. Based on the researchers' initial survey, it was found that the number of ARIs in Madat Community Health Center was 1971 people. The purpose of this study is to determine the factors associated with the implementation of the behavior of prevention of ISPA in infants in Madat District Health Center, East Aceh. The research design used in this study was Cross Sectional. The population in this study were 362 people and samples taken by accidental sampling were as many as 52 people. Data collection methods are primary data and secondary data. Data analysis used is binary logistic regression test. The results showed that knowledge had a sig-p value of 0.010 <0.05, sig-p ventilation 0.002 <0.05 and health services had a sig-p value of 0.010 <0.05. Based on the overall influencing factors, the most dominant factor affecting ARI is ventilation with a B value (4,489). The conclusion in this study is that there is the influence of knowledge, ventilation and health services with the application of community behavior in the prevention of ARI, while the variables of occupancy density and family history of women do not have an influence on community behavior in the prevention of ARI.Keywords: behavior factors, disease prevention, acute respiratory, ISPA